Impact on Survival on Interval between Surgery and Adjuvant Chemotherapy in Completely Resected Stage IB-IIIA Lung Cancer - Wang, Bing-Yen (PLoS One, 2016)
BACKGROUND AND OBJECTIVES: Complete surgical resection is recommended for early stage lung cancer, and adjuvant chemotherapy is given for stage IB to IIIA disease. No studies have examined the best timing to administer chemotherapy after surgery in lung cancer. This study was to investigate the optimal timing of adjuvant chemotherapy after surgical resection. METHODS: Data collected from the Taiwan National Health Insurance Research Database between January, 2004 and December, 2010 were retrospectively analyzed. Patients with stage IB to IIIA lung cancer underwent complete surgical resection and adjuvant chemotherapy were included. A total of 1522 patients were included. The patients were divided into 4 groups according to the interval between surgery and chemotherapy: group 1, < 30 days; group 2, 30–45 days; group 3, 46–60 days; group 4 > 60 days. Univariate and multivariate regression analyses were used to identify prognostic factors for overall survival. RESULTS: The numbers of patients in groups 1, 2, 3, and 4 were 153, 161, 290, and 818, respectively. The 5-year survival rate was 41% in group 1, 48% in group 2, 50% in group 3, and 35% in group 4 (p<0.001). The median survival time was 44.50 months in group 1, 59.53 months in group 2, 67.33 months in group 3 and 36.33 months in group 4 (p<0.001) Survival rate is the poorest when chemotherapy is delayed beyond 60 days after surgical resection Multivariate analysis also indicated the interval between surgery and first course of chemotherapy more than 60 days after surgery was an independent risk factor for survival. CONCLUSIONS: Timing of chemotherapy after surgery is associated with poorer survival in lung cancer patients.